Pengaruh Penggunaan TikTok terhadap Self-Esteem dengan Social Comparison sebagai Variabel Mediasi pada Generasi Z di Kota Denpasar - Anak Agung Ayu Meisya Dewi; Nofha Rina (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
TikTok has become the dominant social media platform among Generation Z in Denpasar City. Its use has the potential to influence self-esteem through social comparison. This study examines the effect of TikTok use on self-esteem with social comparison as a mediating variable. Using a quantitative descriptive approach with SEM-PLS analysis on 383 TikTok users aged 18–24 years in Denpasar City. The study findings indicate that TikTok use has a significant positive effect on self-esteem (β = 0.632) and on social comparison (β = 0.421). Social comparison also has a significant negative effect on self-esteem (β = −0.089) and partially mediates the relationship between TikTok use and self-esteem (β = −0.038). These findings support Social Comparison Theory, which states that social media engagement can strengthen self-identity but also lead to upward comparisons that suppress self-confidence. Practically, the results of this study can provide important input for educational institutions and parents to emphasize the need for developing digital literacy and implementing empathetic communication strategies. With this approach, social media like TikTok can be used as a healthy and constructive space for self-expression for Generation Z.